Korelasi Dukungan Teman Sebaya dengan Praktik Pemeriksaan Payudara Sendiri (SADARI) pada Remaja - Nila Meisarah Fatmasari; Umi Aniroh (Pro Health Jurnal Ilmiah Kesehatan, 2021)
Breast cancer is the most common cancer and the second leading cause of death globally. Teenagers also need to do a regular breast self-examination (BSE) as an effort to prevent and detect early. One of the factors that support adolescents doing a breast self-examination (BSE) is peer support. The purpose of this study was to determine the relationship between peer support and breast self-examination (BSE) in Jambu Village Semarang District adolescents. This research design is analytic correlational with the cross-sectional approach with a sample size of 51 respondents using the purposive sampling method. The data collection tool uses a questionnaire.Â  Data analysis using 25 IBM SPSS Statistics program. Bivariate analysis was processed using the Chi-Square test. The results obtained from the p-value of peer support with breast self-examination practice (BSE) in late adolescent were 0.000<0.05 (Î±). There is a significant relationship between peer support and the practice of breast self-examination (BSE) in adolescents. Hopefully, this research can be providing information for adolescents about the benefits of peer support that can improve the practice of breast self-examination (BSE) inÂ  adolescence.